2019
DOI: 10.3390/metabo9100197
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Metabolite Diversity of the Endophyte Dimorphosporicola tragani

Abstract: Fungi are one of the most prolific sources of microbial secondary metabolites. The production of new metabolites can be achieved using multiple fermentation conditions and by adding small-molecule effectors, including epigenetic modifiers. In the framework of our Natural Product screening programme targeting the discovery of new antimicrobial compounds, we applied multiple fermentation conditions and adsorptive polymeric resins on a large collection of fungal endophytes, to increase and stimulate their fungal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…It appeared that bacteria associated with the seaweeds had antibacterial activity against three pathogenic bacteria of poultry: Escherichia coli, Pausterella multocida, and Salmonella pullorum and three pathogenic bacteria of cattle: E. coli, Staphylococcus aureus, and Pseudomonas aeruginosa. Therefore, they are recommended for use in the treatment of poultry and cattle diseases [136]. De Melo et al [138] isolated bacterial endophytes that belonged to the Bacillus genus.…”
Section: Biotransformation Of Ginsenoside Rb1mentioning
confidence: 99%
“…It appeared that bacteria associated with the seaweeds had antibacterial activity against three pathogenic bacteria of poultry: Escherichia coli, Pausterella multocida, and Salmonella pullorum and three pathogenic bacteria of cattle: E. coli, Staphylococcus aureus, and Pseudomonas aeruginosa. Therefore, they are recommended for use in the treatment of poultry and cattle diseases [136]. De Melo et al [138] isolated bacterial endophytes that belonged to the Bacillus genus.…”
Section: Biotransformation Of Ginsenoside Rb1mentioning
confidence: 99%
“…After attaining culture growth at 30 ± 2 • C for 36 h at 150 rpm, bacterial cells were separated by centrifugation at 7,830 rpm (Eppendorf 5430R) to obtain a cell-free culture filtrate. The culture filtrate was then mixed with preconditioned xad-16 resin (10% w/v) (Sigma Aldrich, United States) for increasing titer of the extraction of metabolites due to its high adsorption capacity (González-Menéndez et al, 2019). A slurry of the culture filtrate and the xad-16 resin was prepared at 150 rpm for 2 h at room temperature and then poured into a chromatographic glass column (10 mm diameter × 300 mm length) having a built-in sintered disk at the bottom.…”
Section: Preparation Of Bacterial Culture Filtrate Extractmentioning
confidence: 99%
“…Bacterial culture filtrate extract was obtained in the solution of ethyl acetate and methanol (1:1 v/v), which was passed through the BCFE-trapped XAD 16 resin. XAD resin has an excellent capacity to enrich different biological molecules including phenolic compounds, flavonoids, peptides, antimicrobial, pharmaceuticals, etc., and has been extensively used for the selective extraction of biomolecules from complex microbial culture media (Liu et al, 2016;Salazar et al, 2017;González-Menéndez et al, 2019) and other biological mixtures, such as adlay bran (Yang et al, 2016), apple skin Wang et al (2020), Glycyrrhiza leaves (Dong et al, 2015), and wheat gluten hydrolysates (Yang et al, 2018), as well as extraction of pharmaceuticals in wastewater (Yu and Wu, 2011). Thus, to achieve maximal entrapment of microbial secretions and minimize the interference of residual medium impurities in the crude biomolecule mixture, we specifically used XAD-16 resin to trap the biomolecules secreted by Nocardioides sp.…”
Section: Quantification Of Iaa and Sa In Bcfementioning
confidence: 99%
“…Among various concentration techniques, Amberlite XAD resin trapping of organic compounds gained recent interest and finds application in plant [ 5 , 6 ] marine invertebrate [ 7 , 8 ], and microbial [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] specialized metabolite extraction.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently extended the exploitation of in-situ XAD-16 extraction of mycelium forming microorganisms, actinomycetes and fungi [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], known as the major providers of valuable bioactive compounds [ 19 , 20 ]. Compared to submerged cultivation, we showed that in-situ XAD-16 extraction significantly impacts the diversity and the yields of target compounds [ 9 , 18 ].…”
Section: Introductionmentioning
confidence: 99%